CREATION OF A SYNTHETIC FORWARD POSITION TO DETERMINE THE LEVEL OF COORDINATION DESTRUCTIONS IN THE ECONOMY (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article actualizes the need to develop a methodology for the effective implementation of derivatives in the activities of economic entities. The expediency of creating a methodology of predictive analytics for determining the level of coordination destructions in the economy in the context of the monetary, foreign exchange, stock, and commodity markets is substantiated. This methodology is designed for object-oriented structural modeling to minimize market destructions. It is proposed to define coordination destructions in the economy as a violation of macroeconomic equilibrium in the direction of its non-optimal states. The reason for this is the impossibility of mutually beneficial coordination of economic entities. The consequence of this is the negative dynamics of macroeconomic indicators. The level of coordination destructions in the market is defined as a long unidirectional deviation of the equilibrium values of the parameters of market predicates from their actual values. The presence of coordination destructions proves the inefficiency of market mechanisms of supply and demand in this market.The formation of a synthetic forward position is based on the algorithm for determining the fair forward price of a financial instrument. It is proved that a synthetic forward position is formed through spot parameter rates of one set of financial instruments to determine fair forward parameter rates of another set of financial instruments. This provides systemic links between the structural elements of the economic system and the effective redistribution of financial resources. It is substantiated that a synthetic forward position allows one to determine equilibrium forward exchange rates for the predicates of the monetary, foreign exchange, stock, and commodity markets. A mechanism has been developed for the formation of a synthetic forward position to determine the equilibrium values of the parameters of market predicates. This mechanism is needed to determine the level of coordination destructions in the economy.
Keywords: synthetic forward position, coordination destructions, derivative, macroeconomic equilibrium, financial instrument, fair forward price, market predicate.